Impact of New York State Influenza Mandate on Influenza-Like Illness, Acute Respiratory Illness, and Confirmed Influenza in Healthcare Personnel. (22nd August 2017) - Batabyal, Rachel A.; Zhou, Juyan J.; Howell, Joy D.; Alba, Luis; Lee, Helen H.; Furuya, E. Yoko; Stockwell, Melissa S.; Calfee, David P.; Brown, Claire E.; Craan, Aziza; Saiman, Lisa
Abstract : In 2013, New York State mandated that, during influenza season, unvaccinated healthcare personnel (HCP) wear a surgical mask in areas where patients are typically present. We found that this mandate was associated with increased HCP vaccination and decreased HCP visits to the hospital Workforce Health and Safety Department with respiratory illnesses and laboratory-confirmed influenza. Infect Control Hosp Epidemiol 2017;38:1361–1363